Walker 256 tumour growth causes marked changes of glutamine metabolism in rat small intestine - Lima, MMR; de Mello, MAR; Curi, R. (Wiley-Blackwell, 2002)
The effect of Walker 256 tumour growth on the metabolism of glucose and glutamine in the small intestine of rats was examined. Walker 256 tumour has been extensively used as an experimental model to induce cancer cachexia in rats. Walker 256 tumour growth decreased body weight and small intestine weight and length. The activities of glucose-6-phosphate dehydrogenase and phosphate-dependent glutaminase were reduced in the proximal, median and distal portions of the intestine. Glutamine oxidation was reduced in the proximal portion only. The decrease in glutaminase activity was not due to a low synthesis of the protein as indicated by Western blotting analysis. Hexokinase and citrate synthase activities were not changed by the tumour. These findings led us to postulate that tumour growth impairs glutamine metabolism of small intestine but the mechanism involved remains to be elucidated. Copyright (C) 2001 John Wiley Sons, Ltd.
Keywords: small intestine; glucose; glutamine; Walker 256 tumour; phosphate-dependent glutaminase